Gen Z Perspective: Phenomenological Study of the Meaning of Economics Subjects in Sharia Accounting Students - Hasan Basri; Reski Wardani; Nur Astaman Putra (CV. Sakura Digital Nusantara, 2026)
Purpose - This study aims to explore the meaning of economics courses in enhancing Sharia economic understanding among Sharia Accounting students. Design/methodology/approach - Using a qualitative phenomenological approach, data were collected through in-depth interviews with students who had completed economics courses. The data were analyzed through thematic analysis to identify essential meanings derived from student’s learning experiences. Finding/Results - The results show that economics courses help students develop systematic and critical thinking in understanding Sharia economics. This improvement is supported by structured learning materials, the integration of conventional economic concepts with Sharia values, and interactive teaching methods. Nevertheless, the learning process is hindered by student’s involvement in various extracurricular activities and their perception of economics courses as an academic burden. This study concludes that economics courses serve not only as introductory subjects but also as strategic conceptual foundations that strengthen student’s holistic understanding of Sharia economics. Originality/Value - This study offers novelty by exploring the lived experiences and meanings of economics subjects among Generation Z students in Sharia Accounting programs through a phenomenological approach. Unlike previous studies that focus mainly on academic achievement or learning outcomes, this research emphasizes how Gen Z students interpret economics subjects within the context of digital transformation, Islamic values, and future career relevance